Chapter 8 A High-Resolution Multi-Scalar Approach for Micro-Mapping Historical Landscapes in Transition - McKee, Arlo; Yuan, May (Leuven University Press, 2021)
"The relational complexity of urban and rural landscapes in space and in time.